Effect of biostimulants on growth and production of cucumber and melon in greenhouse - Gabriel-Ortega, Julio (2024)
Introduction. Biostimulants are organic products that improve plant nutrient absorption, for instance humic substances, amino acids, algae extracts and plant growth- promoting bacteria; and numerous mechanisms and selectivity of specific bostimulants for specific nutrients have been identified. Objetive. Determine the effect of the application of biostimulants on the production of cucumber and melon in the greenhouse. Materials and methods. The biostimulants BioRemedy 2.0 g L-1, Grand Sill 2.0 g L-1, Fossil 5.0 g L-1, L-Amino 2.0 mL L-3 and a Control with application of only water were evaluated in three stages of crop development. The experiment was established as a completely randomized unbalanced experimental design with 10 treatments. Each experimental unit consisted of three rows. The response variables were: plant height, stem thickness, number of fruits, fruit size, fruit volume and fruit weight (yield). Results. The biostimulants had a better effect on plant height, stem diameter, and fruit volume for cucumber. For the melon, fruit volume and weight were affected by biostimulants. It was found that Fossil showed the best effect for plant height in both species and BioRemedy turned out to be the best for stem diameter, fruit volume, fruit weight and number of fruits. Conclusion. BioRemedy was the best biostimulant for stem diameter, volume and fruit weight for cucumber and melon cultivation. L-amino had the best response for stem diameter in melon.